Dental-elites and the pedagogised career: narrative accounts to inform the professionalisation of aspiring dental occupations - Reed, Deborah Pearl (2020)
This thesis seeks to demonstrate how professional journeys within the dental sector are restricted or enabled by educational and pedagogic strategies and tools. Professions and the position of occupational groups within them are always in flux; dentistry is no exception. Increasingly, there are occupational groups within the dental professions, who pursue professional parity and an equivalent opportunity to influence the dental sector. The research focuses on understanding the elites’ positioning within the dental sector from the perspective of theories of professionalisation and knowledge acquisition. The sociology of the professions provides a background which shows how occupations differentiate, some acquiring professional status and others not. The research is located within the sociology of education using the concepts of Basil Bernstein to analyse professional enculturation, in terms of what is transferred during exclusive dental-elite professional educational exchanges, with peers and superiors, which steer knowledge gathering over the course of a professional lifetime. The practical aim of the research is to inform the professional journeys of other aspiring dental occupations seeking to achieve elite, that is to say, influential positions in the future. The research questions were: (1) How are the professional journeys of influential dental sector elites characterised? (2) What typifies the relationship between powerful and dominant agents/ agencies that influence the formation, distribution and communication of professional knowledge in dentistry and those who go on to establish elite professional positions within the dental sector? (3) What are the implications of a Bernsteinian analysis for the emerging professionalising dental occupations? These questions were generated from my own experiences, both as a registered dental professional and as a researcher and also from a consideration of social theories which align with my beliefs, assumptions and values.